Priority Management of Fiber Suitcase Spare Part Warehouse Using 5S Method and Analytical Hierarchy Process (AHP) - Novrisal, Dimas; Hamidah, Luthfia (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
This research discusses the warehouse management of fiber luggage spare parts at PT Artlyn Kreasi Mandiri using the 5S method and Analytical Hierarchy Process (AHP). The problem that occurs is the messy arrangement of spare parts in the warehouse which results in losses due to damage to spare parts and makes it difficult for employees to do their jobs. Effective warehouse management is considered crucial in improving the efficiency and effectiveness of company operations. In this context, the 5S method is used to understand the qualitative aspects of warehouse management, while the AHP method is used for decision-making. The results on 5S indicate the need for improvement of warehouse working environment conditions to reduce spare part damage and increase operational efficiency. In addition, the application of the 5S concept in the warehouse is expected to improve the efficiency and effectiveness of spare parts warehouse management. The AHP calculation results provide weights for each criterion and alternative that support decision making. From the AHP calculation results, it can be concluded that moving to a new warehouse has a higher global weight (0.749) compared to optimizing the existing warehouse (0.251), so moving to a new warehouse is considered a more optimal warehousing strategy for the company